Systematic Literatur Review : Seberapa Penting Disclosure Tone? Efek Disclosure Tone Terhadap Reaksi Investor - Sari, Ni Wayan Diah Puspita (Jurnal Ilmiah Raflesia Akuntansi, 2024)
This research aims to explain the relationship between disclosure tone and investor reaction, which is also reflected in stock returns and firm value. This study employs a systematic literature review approach. The researcher identified 11 articles that met the established criteria for review. Based on the review results, there is a significant positive relationship between disclosure tone and investor reaction, stock returns, and firm value. A more optimistic or positive tone can build investor confidence, thereby influencing stock prices and firm value. Further research on the impact of disclosure tone is needed, particularly in developing countries such as Indonesia.